MicroRNA-21 induces resistance to 5-fluorouracil by down-regulating human DNA MutS homolog 2 (hMSH2) - Valeri, Nicola (National Academy of Sciences, 2010)
The overexpression of microRNA-21 (miR-21) is linked to a number of human tumors including colorectal cancer, where it appears to regulate the expression of tumor suppressor genes including p21, phosphatase and tensin homolog, TGFβ receptor II, and B-cell leukemia/lymphoma 2 -associated X protein. Here we demonstrate that miR-21 targets and down-regulates the core mismatch repair (MMR) recognition protein complex, human mutS homolog 2 (hMSH2) and 6 (hMSH6). Colorectal tumors that express a high level of miR-21 display reduced hMSH2 protein expression. Cells that overproduce miR-21 exhibit significantly reduced 5-fluorouracil (5-FU)-induced G2/M damage arrest and apoptosis that is characteristic of defects in the core MMR component. Moreover, xenograft studies demonstrate that miR-21 overexpression dramatically reduces the therapeutic efficacy of 5-FU. These studies suggest that the down-regulation of the MMR mutator gene associated with miR-21 overexpression may be an important clinical indicator of therapeutic efficacy in colorectal cancer.